GAMELAN ANCAG-ANCAGAN IN ACI PANGILEN DEWA YADNYA: A Religious and Cultural Approach - I Wayan Sukadana; Ida Bagus Gde Yudha Triguna; I Gusti Bagus Wirawan (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The performance of Gamelan Ancag-ancagan in Aci Pangilen Dewa Yadnya in Kesiman shows the phenomenon of art in a unique and distinctive religious ritual. The struggle for aesthetic, mystical, and magical values in religious rituals that have the supreme dimension emphasizes the complexity of phenomena so that it is interesting to explore them in depth. This research prioritizes field studies by applying qualitative methods based on religious and cultural approaches. The results of this study indicate that the reasons underlying the performance of Gamelan Ancag-ancagan in Aci Pangilen Dewa Yadnya in Kesiman include ideological, magical-religious, aesthetic-religious, and sociological reasons. The form of the performance can be classified into two, namely the physical form as a sacred gamelan and the dynamic form as an accompaniment to religious rituals. The function of performance includes aesthetic, religious, and mystical function. The meaning of the performance is revealed from the specific symbols of this gamelan, namely the ancag-ancagan which symbolizes swadharma, the gegedig telu which symbolizes the Tri Loka, Tri Kona, and Tri Wisesa, and the laluangan which symbolize the movement back towards the Highest Reality. The main finding of this study is that Gamelan Ancag-ancagan is a sacred gamelan typical of Kesiman which is only used for Aci Pangilen Dewa Yadnya, not for other religious rituals, let alone profane activities.